Emerging legal issues in banking operations - (:unkn) unknown (IGI Global, 2013)
This chapter deals with legal issues in banking activities, which have gained interest during the past decade. It determines the place of legal issues related to banking activities, such as consumer loans, credit cards, and electronic banking, which all have gained even more importance after the last global financial crisis. The chapter focuses on the comparative analysis of current legal issues in Turkey and in the European Union and the legal issues related to risks in the sphere of electronic banking and suggests potential strategies. © 2014 by IGI Global. All rights reserved.